2017
DOI: 10.1111/cwe.12193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parental Migration on the Academic Performance of Left‐behind Middle School Students in Rural China

Abstract: China's rapid development and urbanization over the past 30 years have caused large numbers of rural residents to migrate to urban areas in search of work. This has created a generation of children who remain behind in rural areas when their parents migrate for work. Previous research has found mixed impacts of parental migration on the educational achievement of left-behind children (LBC), perhaps because of methodological deficiencies and lack of recognition of the heterogeneity of this population of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…The relationships between parental migration and left-behind children's educational outcomes are complicated by the different mechanisms through which migration can exert effects on those relationships. One the one hand, parental migration entails parental absence, which results in the lack of parental care and supervision, and therefore, leads to lower school attainment and poor academic performance (Lee, 2011;Li et al, 2017;Lu & Treiman, 2007;Meng & Yamauchi, 2017;Song et al, 2018;Wu & Zhang, 2017;Zhang et al, 2014;Zhou, Murphy, & Tao, 2014). On the other hand, parental migration increases household income, which reduces child labor and also enables more resources to be invested in a child's human capital (Bai et al, 2018;Bryant, 2005;Chen et al, 2009;Dimova, Epstein, & Gang, 2015;Edwards & Ureta, 2003;Hanson & Woodruff, 2003;Kandel & Kao, 2001;Kuhn, 2006;Lu & Treiman, 2007;Mansuri, 2006).…”
Section: Paternal Migration and The Left-behind Children's Educatiomentioning
confidence: 99%
See 3 more Smart Citations
“…The relationships between parental migration and left-behind children's educational outcomes are complicated by the different mechanisms through which migration can exert effects on those relationships. One the one hand, parental migration entails parental absence, which results in the lack of parental care and supervision, and therefore, leads to lower school attainment and poor academic performance (Lee, 2011;Li et al, 2017;Lu & Treiman, 2007;Meng & Yamauchi, 2017;Song et al, 2018;Wu & Zhang, 2017;Zhang et al, 2014;Zhou, Murphy, & Tao, 2014). On the other hand, parental migration increases household income, which reduces child labor and also enables more resources to be invested in a child's human capital (Bai et al, 2018;Bryant, 2005;Chen et al, 2009;Dimova, Epstein, & Gang, 2015;Edwards & Ureta, 2003;Hanson & Woodruff, 2003;Kandel & Kao, 2001;Kuhn, 2006;Lu & Treiman, 2007;Mansuri, 2006).…”
Section: Paternal Migration and The Left-behind Children's Educatiomentioning
confidence: 99%
“…Because of the different roles fathers and mothers play in a household, paternal and maternal migration exerts different total effects on a child's educational outcomes. Yet only a few empirical studies considered separately the two types of migration while using Chinese data (Bai et al, 2018;Chen et al, 2009;Li et al, 2017;Meng & Yamauchi, 2017;Wang, 2014;Zhao et al, 2014). Of those studies, their estimates are often infected by having small sample sizes in each category of household migration status, especially in the category of households with migrant mother and nonmigrant father, and thus are prone to lack statistical power and stability.…”
Section: Paternal Migration and The Left-behind Children's Educatiomentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to long-term parent-child separation, parental migration has a negative impact on children's academic achievements (Wang and Mesman 2015;Zhao and Yu 2016). Academic problems of left-behind children have become a research focus over the past decade (Roy et al 2015;Li et al 2017;Bai et al 2018). McKenzie and Rapoport (2011) found that family migration reduces the educational attainments of the rural Mexican children.…”
Section: Introductionmentioning
confidence: 99%